Effort in Semi-Automatized Subtitling Processes: Speech Recognition and Experience during Transcription - Tardel, Anke (Journal of Audiovisual Translation, 2020)
The presented study investigates the impact of automatic speech recognition (ASR) and assisting scripts on effort during transcription and translation processes, two main subprocesses of interlingual subtitling. Applying keylogging and eye tracking, this study takes a first look at how the integration of ASR impacts these subprocesses. 12 professional subtitlers and 13 translation students were recorded performing two intralingual transcriptions and three translation tasks to evaluate the impact on temporal, technical, and cognitive effort, and split-attention. Measures include editing time, visit count and duration, insertions, and deletions. The main findings show that, in both tasks, ASR did not significantly impact task duration, but participants had fewer keystrokes, indicating less technical effort. Regarding visual attention the existence of an ASR script did not decrease the time spent replaying the video. The study also shows that students were less efficient in their typing and made more use of the ASR script. The results are discussed in context of the experiment and an outlook on further research is given.